Skinning and blending with rational envelope surfaces. (June 2017) - Bizzarri, Michal; Lávička, Miroslav; Kosinka, Jiří
Abstract: We continue the study of rational envelope (RE) surfaces. Although these surfaces are parametrized with the help of square roots, when considering an RE patch as the medial surface transform in 4D of a spatial domain it yields a rational parametrization of the domain's boundary, i.e.,  the envelope of the corresponding 2 -parameter family of spheres. We formulate efficient algorithms for G 1 data interpolation using RE surfaces and apply the developed methods to rational skinning and blending of sets of spheres and cones/cylinders, respectively. Our results are demonstrated on several computed examples of skins and blends with rational parametrizations. Highlights: We continue the study of rational envelope (RE) surfaces. We formulate efficient algorithms for G 1 data interpolation using RE surfaces. We apply RE surfaces to rational skinning and blending.